Osteoprotegerin and Interleukin-37 are Correlated with Liver Diseases in Chronic Hepatitis B Virus (HBV)-infected Subjects - Sadoun Abbas Alsalimi; Idries Muhson Abeed Al-Mashkor; Adnan Jassim Mohammed Al-Fartosy (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Various biological markers have been proposed to predict subclinical events in subjects with chronic hepatitis B virus (HBV). However, studies regarding chronic HBV infection are still limited. The current study aimed to investigate the relationship between osteoprotegerin (OPG) and interleukin-37 (IL-37) serum levels in chronic HBV subjects.METHODS: Sixty subjects with chronic HBV infection without previous treatment and 30 healthy subjects were included in this study. Blood samples were withdrawn and examined for biochemical parameters through the use of enzyme-linked immunosorbent assay (ELISA) assessments. Moreover, anthropometric estimations and medical histories were performed on all subjects through a standard self-administered questionnaire.RESULTS: A highly significant elevation (p<0.01) in serum levels of alanine transaminase (ALT), aspartate transaminase (AST), and IL-37 and a significant increase (p<0.05) in serum level of OPG were observed in chronic HBV subjects compared with the controls. The data demonstrated that OPG had a positive correlation with IL-37 and that both OPG and IL-37 had significantly positive correlations with ALT and AST. Furthermore, the area under the receiver operating characteristics (ROC) curve (AUC) was computed for ALT, AST, OPG, and IL-37 (AUC = 0.831, 0.829, 0.608, and 0.618, respectively) which could be potentially greater predictive biomarkers in chronic HBV subjects.CONCLUSION: The positive correlation of OPG and IL-37 with ALT and AST and the high positive value of AUC for OPG and IL-37 shows that OPG and IL-37 could to be potential inflammatory biomarkers for the early onset of liver disease and hepatocellular carcinoma in chronic HBV-infected subjects.KEYWORDS: osteoprotegerin, interleukin-37, hepatitis B virus, inflammation, liver